Case report: Dancing in the dark: A critical single case study engaging a blind father in the rehabilitation journey of his visually impaired child - Provenzi, Livio; Pettenati, Giada; Luparia, Antonella; Paini, Daria; Aprile, Giorgia; Morelli, Federica; Mascherpa, Eleonora; Vercellino, Luisa; Grumi, Serena; Signorini, Sabrina (Frontiers in Psychology, 2022)
Background. Face-to-face visual contact is a key component of the early parent-child interaction, therefore a visual impairment condition of the parent or the child represents a risk factor for dyadic patterns’ development. Aims. The study presents a critical single case of a blind father and a 18-month-old visually impaired child. The study aims to explore changes in the relational functioning of this dyad during an early family-centered intervention. Methods and Procedures. Ten parent-child sessions were videotaped and micro-analytically coded. Data were analyzed through a State Space Grid crossing child’s social cues and types of father verbalizations. Outcomes and Results. Findings showed a stable increase in the amount of child social cues over time. Moreover, the dyad exhibited progressive changes in dyadic regulation, stability, and organization. The measure return time to the “active interaction” region of interest decreased progressively. A reduction was observed also for the time spent by the dyad in the region “no vocal contact”. Conclusions and Implications. This critical single case highlighted the benefits of parental engagement in early interventions for the dyadic regulation in parent-child interaction.